The Infography of Indonesia Agency for Creative Economy as Information Dissemination and Branding Media for Creative Economy of Regencies/Cities in Indonesia - Gunawan Wiradharma; Melisa Arisanty; Dede Mahmudah (BPSDMP Kominfo Manado, 2021)
Indonesian Agency of Creative Economy (Bekraf) has done Independent Scoring for Creative Regencies/Cities in Indonesia (PMK3I) as one of the efforts to boost creative economic growth in every regency/city in Indonesia. The scoring result is then released in a form of infographes which shows comprehensive information about creative economy potentials in every regency/city in Indonesia. Regencies/cities can also use the infographies as a media for branding dan strategies to foster creative economy in their areas. Therefore, this reseach is aimed to describe the functions of infographes in disseminating imformation and strategies for creative economic branding in regencies/cities in Indonesia. This reseach is conducted using qualitative approaches and thorough interviews with resource persons as sampling data methode. The interviews are about compiling the infographies and analysing the content of the infographies from PMK3I which has been published in www.kotakreatif.id. The results of this research has shown that infographies are used not only as a media for disseminating information, but also as a media for city branding in order to increase society's brand awareness of the most potential and main subsector in a regency/city in Indonesia.